Comparison of few E-databases in the Field of Dental Sciences: a Study - Vinod Kumar, B. L. (Journal of Information and Knowledge, 2014)
An attempt is made to compare the electronic databases, which covers the dental science discipline. A comparative study is made with six databases namely Science Direct, Ovid, Blackwell-synergy, Web of Science, Emerald and EBSCO. The findings reveal that, all the resources are clearly focused on their respective disciplines by fulfilling the information needs of the targeted users. As per the subjects covered by the databases, it is summarized in Table 1. This study gets more utility by identifying and including more parameters for comparing information resources. Also search features are to be critically examined with user interfaces in each of the resources to judge that resources are more user friendly and have better search functionalities.